ChemInform Abstract: Sodium Selenite Pentahydrate, Na2SeO3·5H2O. Issue 4 (28th January 2014) - Mereiter, Kurt
Abstract Single crystals of Na2SeO3·5H2O are grown by evaporation of an aqueous solution of Na2SeO3.